If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(5 + n) = 19 + 3n (5 * 5 + n * 5) = 19 + 3n (25 + 5n) = 19 + 3n Solving 25 + 5n = 19 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 25 + 5n + -3n = 19 + 3n + -3n Combine like terms: 5n + -3n = 2n 25 + 2n = 19 + 3n + -3n Combine like terms: 3n + -3n = 0 25 + 2n = 19 + 0 25 + 2n = 19 Add '-25' to each side of the equation. 25 + -25 + 2n = 19 + -25 Combine like terms: 25 + -25 = 0 0 + 2n = 19 + -25 2n = 19 + -25 Combine like terms: 19 + -25 = -6 2n = -6 Divide each side by '2'. n = -3 Simplifying n = -3
| (3/2)(2x+2)=6 | | 15/(2x)=3/(5+x) | | x-2(2-2x)=2x+9 | | -2(x+1)=-2x-2 | | 15/2x=3/5+x | | -7(z-5)=-8z | | 2n+12=1 | | 2a^3+162a=0 | | X/6=20 | | 3x+4=4(x+8) | | -(4z-(10z+1))=1+(5z+2) | | 25s^2-10sd+d^2= | | 4.5x-12=24 | | 4g=3 | | -9=12+x | | 24/y-x | | -9=-x-8x | | 2(x+5)+2(x-3)=(x+2)+(3x-11)+(3x-11) | | 2z+4z=5z-1 | | 9/11x-1/11 | | 6(v+8)=-5(2v-8)+4v | | 27=12-2(x+2) | | 3(2y+4)=5(3y+6) | | 2(-4+2p)+3p=-5+4p | | -4d+2(3+d)=-1 | | 2(k-(2k+7)+6)=2(k+1) | | logx+(x+6)=2 | | 4x/5+6x/10=-12 | | m+5/12 | | 7-3(1-4p)=76 | | 6(-3x+4)=-10x+8 | | 6(9+x)=5(9+x) |